2019
DOI: 10.1186/s40729-019-0182-6
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study to identify associations between clinician training and dental implant outcome and to compare the use of MATLAB with SAS

Abstract: Background The aim of this study was to identify any associations between predictor variables, mainly clinician training and dental implant outcome, among the residents in different departments and to compare statistical analysis with the use of MATLAB R2017a™ to SAS version 9.4. Methods Dental records were reviewed from January 1, 2011, to December 31, 2015. Two thousand forty-eight dental implants were placed on 471 patients seen by residents from the departments of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…However, another study verified no association between implant loss and different variables such as bone augmentation, time of implant placement, diabetes and smoking, corroborating our results [15]. Besides, in a previous study several parameters similar to those evaluated here did not yield any significant association with implant failures [16].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, another study verified no association between implant loss and different variables such as bone augmentation, time of implant placement, diabetes and smoking, corroborating our results [15]. Besides, in a previous study several parameters similar to those evaluated here did not yield any significant association with implant failures [16].…”
Section: Discussionsupporting
confidence: 90%
“…The success rate for Harvard School of Dental Medicine periodontology residents was 96.48% during the 4-year study period [17]. Nonetheless, an interesting study analyzed the implant outcomes and the clinical training at Louisiana State University Health Science Centera (USA), showing that the advanced group (94.2%) had the best implant outcomes followed by the intermediate group (89.38%) and beginner group (88.6%) clearly demonstrating that increased clinician training improves clinical outcomes [16]. Moreover, an interesting analysis demonstrated that clinicians' age and years of experience as dentists or as specialist were not found to be predictors to early implant failure rate however, the number of implants placed during the postgraduate training was found to be significantly predicting early failure rate of implants [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was suggested that the dentist’s years of experience, implant training, and postgraduate specialization might affect the knowledge, attitude, and way of practice of dental implants [ 5 ]. Sonkar et al [ 6 ] reported a higher survival rate of 94.14% for residents in periodontology, followed by residents in prosthodontists (91.48%) and residents in maxillofacial oral surgeons (89.64%). The survival rates of implants improved by year of training: third year periodontics and oral surgeons 94.2%, second year 89.38%, and first year 88.6%.…”
Section: Introductionmentioning
confidence: 99%
“…This pilot study provides information to clinicians about the outcome of ARP by postgraduate students in a university setting. Less favourable outcomes have been demonstrated in implant procedures by less experienced clinicians, and it is interesting to observe the differences in ARP between training clinicians in this study and other reported data from experienced clinicians [ 21 ].…”
Section: Introductionmentioning
confidence: 68%